Brassica rapa hairy root based expression system leads to the production of highly homogenous and reproducible profiles of recombinant human alpha‐L‐iduronidase. Issue 2 (30th August 2018) - Cardon, Florian; Pallisse, Roser; Bardor, Muriel; Caron, Aurore; Vanier, Jessica; Ele Ekouna, Jean Pierre; Lerouge, Patrice; Boitel‐Conti, Michèle; Guillet, Marina
Summary: The Brassica rapa hairy root based expression platform, a turnip hairy root based expression system, is able to produce human complex glycoproteins such as the alpha—L—iduronidase (IDUA) with an activity similar to the one produced by Chinese Hamster Ovary (CHO) cells. In this article, a particular attention has been paid to the N ‐ and O ‐glycosylation that characterize the alpha‐L‐iduronidase produced using this hairy root based system. This analysis showed that the recombinant protein is characterized by highly homogeneous post translational profiles enabling a strong batch to batch reproducibility. Indeed, on each of the 6 N ‐glycosylation sites of the IDUA, a single N ‐glycan composed of a core Man3 GlcNAc2 carrying one beta(1, 2)‐xylose and one alpha(1, 3)‐fucose epitope (M3XFGN2) was identified, highlighting the high homogeneity of the production system. Hydroxylation of proline residues and arabinosylation were identified during O‐ glycosylation analysis, still with a remarkable reproducibility. This platform is thus positioned as an effective and consistent expression system for the production of human complex therapeutic proteins.